Rater’s intention towards appraising accurately - Embi, Muhamad Ali; Low, Kah Choon (Universitas Muhammadiyah Yogyakarta, 2014)
The aim of this article is to stimulate thoughts and introduce new prospects to the study of performance appraisal accuracy, especially in the raters’ perspective.It focuses on a relatively understudied aspect of performance appraisal which is raters’ intention towards appraising accurately. In order to understand the application of this aspect, this paper attempts to develop a conceptual framework based on hypotheses of the direct and indirect factors that predict the raters’ intention to appraise accurately. It is hypothesized that the raters’ experience in appraising, raters’ perceived purposes of appraisal, and raters’ perceived information adequacy for appraising will predict the raters’ intention towards appraising accurately by influencing the raters’ attitude towards appraising accurately, raters’ perceived subjective norms towards appraising accurately, and raters’ perceived behavioral control towards appraising accurately.